2021
DOI: 10.1039/d1ra00439e
|View full text |Cite
|
Sign up to set email alerts
|

Constructing helical nanowires via polymerization-induced self-assembly

Abstract: Helical nanowires were successfully synthesized through polymerization-induced self-assembly and subsequent aging. The achiral BCP nano-objects underwent a morphology transition from spheres to helical nanowires during aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Shen et al . observed that helical nanowires can be developed based on an achiral system via PISA of a fluorinated random copolymer [84] . Ultralong nanowires with multiple‐strand helices were readily observed in a wide range of block compositions.…”
Section: Supramolecular Chiral Expression and Morphology Control By P...mentioning
confidence: 99%
“…Shen et al . observed that helical nanowires can be developed based on an achiral system via PISA of a fluorinated random copolymer [84] . Ultralong nanowires with multiple‐strand helices were readily observed in a wide range of block compositions.…”
Section: Supramolecular Chiral Expression and Morphology Control By P...mentioning
confidence: 99%
“…The strategy of chain extension from fluorinated macro-CTAs has also allowed the facile preparation of spherical FPNPs of low PSD with poly­(MMA) cores (CO 2 -phobic) and fluorinated shells (CO 2 -philic) via the PISA process under scCO 2 conditions . The employment of fluorinated copolymers of poly­(DMEMA)- co -poly­(TFEMA) as macro-CTAs was also investigated in RAFT-mediated PISA in ethanol, yielding helical nanowires using poly­(13FOMA) as the second block …”
Section: In Situ Synthesis Of Fpnps Via Rdrpsmentioning
confidence: 99%
“…Other strategies toward anisotropic structures involve using host‐guest complexation 204–206 or liquid crystalline block copolymers based on, for example, fluorinated repeat units 207–209 …”
Section: Advances Of Pisa For Potential Future Ddsmentioning
confidence: 99%
“…200 Other strategies toward anisotropic structures involve using host-guest complexation [204][205][206] or liquid crystalline block copolymers based on, for example, fluorinated repeat units. [207][208][209] Next to exploiting secondary interactions to imprint directionality, they could also be leveraged for cargo retention in the core. 132,210,211…”
Section: Additional Intra-/intermolecular Interactions To Imprint Dir...mentioning
confidence: 99%